Sosialisasi dan Penyesuaian Minat Bakat Siswa melalui Psikotes pada Siswa Kelas IX MTsS Ar Rahman Paya Tumpi Aceh Tengah - Shaulita, Rizkia; Shaumiwaty, Shaumiwaty; Isnawati, Isnawati (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstrack Interests and talents are the most important part in determining majors for middle and high school students. To continue education according to one's skills, it is important to carry out interest and aptitude psychological tests so that the phenomenon of wrong majors that is often complained about at the tertiary level no longer occurs. Often the basic complaint that students complain about is regret because they chose the wrong major and this resulted in not graduating at college level. This community service is aimed at providing information and knowledge to MTsS Ar Rahman Paya Tumpi students through socialization and also conducting interest and talent psychological tests. This socialization and adjustment of talents is carried out to reduce the number of mistakes in choosing a major for students in the future. The number of subjects included in this service was 26 grade 9 students. The psychological test instruments used in this service were the Wartegg Test, RMIB (Rothwell Miller Interest Blank), Modality Test, and Dragon Test. The result of this community service is that it is able to provide an overview of students' interests and talents as well as an overview of knowledge regarding the student's level of intelligence and personality. From the results of the tests that have been carried out, students can use them to proceed to the next stage, such as choosing a major, both at the high school level and also at the tertiary level, and students are able to understand themselves and their personalities. Socialization of the importance of taking interest and talent tests was also explained as important information for students at MTsS Ar Rahman Paya Tumpi. Keywords: Socialization and adjustment, Talent Interest. Psychological test.